Collaborative Environmental Management to Support Sustainable Tourism During the Covid 19 Pandemic (Case Study in Pulo Geulis Tourism Village) - Annisa Wardhani; Fauzi Mubarak; M. Iqbal Katik Rajoendah (Indonesian Journal of Social Work, 2022)
The tourism sector is the sector that has most felt the impact of the Covid 19 pandemic. Travel restrictions and crowds issued by the Indonesian government during the early 2020 pandemic are still being carried out. Several tourist destinations/areas try to maintain their sustainability with various efforts and stimuli to increase tourist visits, one of which is the Pulo Geulis Tourism Village/Thematic Village which is famous for its mural paintings. The Pulo Geulis area represents cultural diversity as well as a very strong tolerance since ancient times. The existence of this area can be a strong magnet for the development of leisure tourism as well as to support business tourism activities (MICE). The management of the Pulo Geulis Tourism Village is carried out in a collaborative manner that actively involves educational institutions, corporations and also tourism communities/groups such as tourism awareness groups (Pokdarwis) as well as internal community organizations in the area. During the pandemic, the area structuring activities that have been carried out by several stakeholders must gradually experience delays. Initiation to restart environmental management activities begins with reforestation activities in the area. This study will explore forms of collaboration and partnership (partnership) and the role of each stakeholder in environmental management activities in the Pulo Geulis Tourism Village during the Covid 19 Pandemic. The method used in this research is a case study of environmental management activities involving local governments, institutions education, company and community/society. The output of this research is the mapping of roles and forms of collaboration of relevant stakeholders (such as technical/ non technical support, knowledge sharing, community empowerment/ engagement, networking dan local community knowledge) involved in environmental management activities in the Pulo Geulis Tourism Village.